POTENSI CURCUMIN DALAM EKSTRAK RIMPANG KUNYIT (CURCUMMA DOMESTICA L.) SEBAGAI MODALITAS PENCEGAHAN PREEKLAMSIA PADA IBU HAMIL DENGAN RESISTANSI INSULIN - Wibawa, I Made Bagus Cahya; Putra, Agus Indra Yudhistira Diva; Tandiono, Erick Kusuma (Essential: Essence of Scientific Medical Journal, 2019)
Introduction: Preeclampsia is a pregnancy disorder characterized by significantly increased blood pressure (systolic pressure ?140 mmHg, diastolic pressure ?90 mmHg) induced by pregnancy and proteinuria. Preeclampsia is often associated with hyperglycemic state, and studies found that hyperglicemia increases the risk of preeclampsia up to three times higher. Discussion: There are correlations between insulin resistance and glucose intolerance with preeclampsia, shown by the statistics that 20% and 15% of pregnant women with DM Type 1 and Type 2 respectively will develop preeclampsia. Excessive glucose level could induce intracellular changes in cytotrophoblasts that causes placental abnormalities and leads to preclampsia. Recent studies found that hyperglicemia treatment could reduce the risk of preeclampsia up to 54% (RR:0,46;95% CI:0,22-0,97). Turmeric extract contains curcumin that is known for its antidiabetic activity. Curcumin can reduce the insulin resistance and glucose intolerance by inhibition of ROS production to maintain the viability of islet cells, suppression of inflamatory cytokines (TNF-?, IL-6, NFkB) production, stimulation of glucose transporter (GLUT-4) expression and glucose clearance, and suppression of FFA level. Conclusion: Curcumin is potential to be used as a new modality to prevent preeclampsia on women with insulin resistance and glucose intolerance, but the exact amount of turmeric extract or curcumin concentration needed to achieve the desired effect is still unknown.